Polariton Resonances for Ultrastrong Coupling Cavity Optomechanics in GaAs/AlAs Multiple Quantum Wells - Jusserand, B. (2015)
Polariton-mediated light-sound interaction is investigated through resonant Brillouin scattering experiments in GaAs/AlAs multiple-quantum wells. Photoelastic coupling enhancement at exciton-polariton resonance reaches 105 at 30 K as compared to a typical bulk solid room temperature transparency value. When applied to GaAs based cavity optomechanical nanodevices, this result opens the path to huge displacement sensitivities and to ultrastrong coupling regimes in cavity optomechanics with couplings g0 in the range of 100 GHz.